A rare case of synovial osteochondromatosis of the elbow - Loong, Loh Li; Ann, Wong Kai; Zakaria@Mohamad, Zamzuri (2019)
Synovial osteochondromatosis is an unusual, rare and benign tumour. This disease is characteristically monoarticular, most commonly found in knee joint, however it is rarely found in the elbow. A 49-year-old Indian man presented to hospital with a 6-month history of pain, swelling, intermittent locking, loss of range of motion of right elbow and a considerable size of elbow with no recollection of associated trauma. Plain radiographs of right elbow showed numerous radiopaque round and oval loose bodies within the right elbow joints. Computer Tomographic (CT) scan showed multiple bony mass within the right elbow joint. Arthroscopic synovectomy, debridement, excisional biopsy and loose body removal combined with mini-arthrotomy of the right elbow was performed due to limited exposure for removal of larger loose bodies. Histopathological examination of the tissue sample is consistent with the diagnosis of synovial osteochondromatosis. The clinical and radiological evaluation at 6th month postoperatively showed marked reduction in the volume of the elbow, further improvement of elbow range of motion of this patient and the Mayo elbow performance score before surgery and at 6 months postoperative, with an increase from 50 to 80 points. Synovial osteochondromatosis of the joints is a rare condition. The signs and symptoms are not specific and may be suggestive of other pathology conditions. Arthroscopic synovectomy and removal of loose body is the standard operative procedure till today. However, combination of arthroscopy and mini-arthrotomy in cases of large loose bodies may provide a good clinical and functional outcome.